2010
DOI: 10.1097/ede.0b013e3181cb41f7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Error in Using Ambient PM2.5 Concentrations as Proxies for Personal Exposures: A Review

Abstract: Background Several methods have been used to account for measurement error inherent in using ambient concentration of particulate matter < 2.5 μm/m3 (PM2.5) as a proxy for personal exposure. Such methods usually rely on the estimated correlation between ambient and personal PM2.5 concentrations (r). These studies have not been systematically and quantitatively assessed for publication bias or heterogeneity. Methods We searched seven electronic reference databases for studies of the within-participant correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 46 publications
4
70
0
1
Order By: Relevance
“…Our findings suggest that the concentrations measured at fixed sites are likely to correspond with the concentrations measured outside homes within a 5-km radius. However, people spend approximately 85% of their time indoors (Avery et al, 2010), and our findings were in accordance with the earlier report: the average proportion of each day our participants undergoing personal monitoring spent indoors during summer and autumn was 84%. Therefore, it is clear that a significant portion of total personal exposure to PM occurs in the indoor environment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings suggest that the concentrations measured at fixed sites are likely to correspond with the concentrations measured outside homes within a 5-km radius. However, people spend approximately 85% of their time indoors (Avery et al, 2010), and our findings were in accordance with the earlier report: the average proportion of each day our participants undergoing personal monitoring spent indoors during summer and autumn was 84%. Therefore, it is clear that a significant portion of total personal exposure to PM occurs in the indoor environment.…”
Section: Discussionsupporting
confidence: 93%
“…Although many studies have investigated the correlations between fixed-site and personal PM and NO 2 concentrations (Avery et al, 2010;Lai et al, 2004;Sarnat et al, 2000), they focused on short-term PM and NO 2 exposure. Similar investigations of long-term exposure to pollutants, particularly to PM, are sparse, so the results of the present study are valuable in clarifying any bias caused by the use of fixed-site measurements as proxies for individual exposure in studies of the effects of long-term PM and NO 2 exposure on health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The change in mortality risk in relation to changes in personal exposure is appreciably greater (30-50%) than the original ACS coefficient indicates, but the fact that indoor PM 2.5 is only a partial determinant of overall PM 2.5 exposure tends to reduce the overall relative "correction" for residential indoor exposure to approximately unity. A modification to the ACS coefficient of around 30% to 50% for total personal exposure is broadly consistent with previously published evidence suggesting increased coefficients for personal exposure in time-series studies [37,38]. Similarly, studies adjusting coefficients for exposure measurement error using regression calibration techniques have tended to suggest that central monitoring sites generally provide a reasonable representation of overall personal exposures [39][40][41].…”
Section: Discussionsupporting
confidence: 86%
“…For many epidemiologic air pollution time series studies, a central monitoring site is used to determine the exposure of study subjects. Previous studies have shown that the ambient concentrations of PM 2.5 at a fixed site can be a good predictor of personal exposure, but the accuracy is dependent on the characteristics of the participants, studies, and environments in which they are conducted (Avery et al 2010). Additionally, the highest PM 10 and PM 2.5 concentrations in European cities occur at roadsides.…”
Section: Introductionmentioning
confidence: 99%